The Regulation and Protection of Genetically Modified Food - Yuwono Prianto; Viony Kresna Sumantri; Swara Yudhasasmita (Fakultas Hukum, Universitas Warmadewa, 2020)
Genetically Modified foods are now being widely consumed. In 2011, more than 90% of corns and soybeans in the US are genetically modified. Research shows in America the people suffering from allergies are increasing. Some people connected the allergies with the widely consumed genetically modified foods. But other researchers show that genetically modified food bring no harms to human. In fact, genetically modified foods are cheaper and will be a great tool to fight against poverty and hunger. But in countries like Italy, Austria, and the Netherlands, they have fully banned genetically modified organisms, making them the GMO’s free Country. In the survey conducted, most consumers are not educated enough about GMO. They also concern about the impact of genetically modified food on human health, environmental and animal health.